Enhancing English’ speaking skill of students in Tunas Baru High School through ICT- integrated news reporting - Pratiwi, Theodesia Lady; Togatorop, Sarah Ayuandri; Putri, Andien Aisyah; Samuel, Samuel; Zaki, Leil Badrah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
There is an increasing importance of English speaking proficiency in today's era and there comes with challenges that students face in mastering this skill. It calls the necessity of enhancing speaking skills for 21st-century learners and proposes an innovative approach— news reporting practice aided by Information and Communication Technology (ICT). The research aims to demonstrate the effectiveness of news reporting as a method to improve students' speaking abilities, leveraging ICT tools such as video creation and platforms like